Penerapan Model Project Based Learning untuk Meningkatkan Kreativitas dan Prestasi Belajar Materi Bangun Datar - Timbul Sasongko (Jurnal Didaktika Pendidikan Dasar, 2024)
The aim of the research is to increase the application of the PjBL model in increasing the creativity and learning achievement of Flat-Round Mathematics for Class IV Semester II Students at SD Negeri 6 Punung for the 2022/2023 Academic Year. This research is a type of classroom action research. The research subjects were 5 students in Class IV of SD Negeri 6 Punung. Data collection: observation, questionnaires, tests, and documentation. Creative success is at least "good" with a conversion of 10.5 ≤ x < 13.5 creative involvement and student learning achievement 70 on a rating scale of 1-100. Data analysis was carried out using qualitative and quantitative. The research results show that (a) the PjBL model can increase student creativity in all indicators, namely discipline, creative work, inspiration and insight, improvisation, imagination, and incubation (b) Student learning achievement increases from average to very high at the end of the cycle.